2020
DOI: 10.2147/ndt.s263424
|View full text |Cite
|
Sign up to set email alerts
|

<p>Serotonin Type 6 and 7 Receptors as a Novel Therapeutic Target for the Treatment of Schizophrenia</p>

Abstract: Schizophrenia is a serious disease of the central nervous system that affects a person’s ability to think, feel and behave clearly. Even though the pathophysiological hypothesis of the disease is not clearly understood, dysfunction of dopamine, glutamate, serotonin and other neurotransmitters is widely believed to be involved. Serotonin within the synaptic vesicles functions as neurotransmitter and neurohormone in regulation of emotion, learning, memory, hormone release, cognition and motor function. Dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Serotonin receptors (5-HTRs) are a group of proteins extensively examined by academic and commercial researchers, due to their vital roles, which they play in the organism, constituting thus important drug targets for a wide range of disorders [1,2]. Their endogenous ligand, serotonin, modulates numerous processes, such as mood, perception, reward, anger, aggression, appetite, memory, sexuality, attention, among others; however, it also controls other, non-neuropsychological processes, such as vasoconstriction, digestion, muscle contraction, and inflammatory mediation [1,[3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotonin receptors (5-HTRs) are a group of proteins extensively examined by academic and commercial researchers, due to their vital roles, which they play in the organism, constituting thus important drug targets for a wide range of disorders [1,2]. Their endogenous ligand, serotonin, modulates numerous processes, such as mood, perception, reward, anger, aggression, appetite, memory, sexuality, attention, among others; however, it also controls other, non-neuropsychological processes, such as vasoconstriction, digestion, muscle contraction, and inflammatory mediation [1,[3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The current classification of serotonin receptors group them into seven classes (5-HT 1-7 ) with a total of 14 members. Except for 5-HT 3 R which is a ligand-gated ion channel, serotonin receptor actions are mediated via G proteins, which makes them representatives of the G protein-coupled receptors (GPCRs) [2,15,16]. All metabotropic 5-HTRs share the same architecture of seven transmembrane domains (TMDs) and one intramembrane helix 8 (H8), which are connected by intra-and extracellular loops (ICLs and ECLs, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction of serotonin pathways has been associated with psychiatric disorders. In schizophrenia, high levels of serotonin have been observed in areas of the anterior cingulate cortex and in the dorsolateral frontal lobe, being associated with the appearance of positive symptoms [ 105 ]. The serotonin hypothesis emerged after studies showed a decrease in hallucinatory behavior and a slowing of the progression of the disorder when drugs that blocked 5-HT2A receptors were administered.…”
Section: The Serotonin Hypothesismentioning
confidence: 99%
“… 5 However, the pathological complexity underlying these changes in serotonin neurotransmission is not clearly understood. 6 9 MDD is a heterogeneous disorder because only 30% to 40% of patients respond to antidepressants. 10 , 11 SCZ also shows heterogeneity, and the understanding of the serotonergic neuropathological effects on the brain is unclear.…”
Section: Introductionmentioning
confidence: 99%